PENERAPAN PENDEKATAN KONSTRUKTIVISME MENGGUNAKAN VIRTUAL LAB UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IX SMP PADA MATERI KEMAGNETAN DAN PEMANFAATANNYA - Khairun Nisa; Yennita Yennita; Ernidawati Ernidawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract : This study aims to describe the outcomes learning of IX SMP students by implementing constructivist approach using virtual lab on magnetism and its uses and to find out the improvement of the outcomes learning of IX SMP students on magnetism and its uses. This research method is quasi experiment (Post-test only control design) applied to student of SMPN 1 Bangkinang Kota and the instrument of this research is cognitive learning outcomes test on magnetism and its uses. The object of this research is experiment class that given any treatment (implementing constructivist approach using virtual lab) and control class that implementing conventional approach. The result of the study shows that learning outcomes of IX SMP students that implementing constructivist approach using virtual lab on magnetism and its uses is higher than the learning outcomes of IX SMP students that implementing conventional approach, and there is also an improvement about the learning outcomes of IX SMP student that implementing constructivist approach using virtual lab on magnetis and its uses.Key Words : Constructivist Approach, Virtual Lab, Learning Outcomes, Magnetism and its uses.